Cross-protocol assessment of induction and durability of VISP/R in HIV preventive vaccine trial participants. - Nicole Espy; Xue Han; Shannon Grant; Esther Kwara; Bharathi Lakshminarayanan; Michael Stirewalt; Kelly E Seaton; Georgia D Tomaras; Erin Goecker; Julie McElrath; Jessica Andriesen; Yunda Huang; et al. (Public Library of Science (PLoS), 2023)
Candidate HIV vaccines are designed to induce antibodies to various components of the HIV virus. An unintended result of these antibodies is that they may also be detected by commercial HIV diagnostic kits designed to detect an immune response to HIV acquisition. This phenomenon is known as Vaccine-Induced Seropositivity/Reactivity (VISP/R). In order to identify the vaccine characteristics associated with VISP/R, we collated the VISP/R results from 8,155 participants from 75 phase 1/2 studies and estimated the odds of VISP/R by multivariable logistic regression and 10-year estimated probability of persistence in relation to vaccine platform, HIV gag and envelope (env) gene inserts, and protein boost. Recipients of viral vectors, protein boosts, and combinations of DNA and viral-vectored vaccines had higher odds of VISP/R compared to those who received DNA-only vaccines (odds ratio, OR = 10.7, 9.1, 6.8, respectively, p<0.001). Recipients of gp140+ env gene insert (OR = 7.079, p<0.001) or gp120 env (OR = 1.508, p<0.001) had higher odds of VISP/R compared to those participants who received no env. Recipients of gp140 protein had higher odds of VISP/R than those that did not receive protein (OR = 25.155, p<0.001), and recipients of gp120 protein, had lower odds of VISP/R than those that did not receive protein (OR = 0.192, p<0.001). VISP/R persisted at 10 years in more recipients of env gene insert or protein compared to those who did not (64% vs 2%). The inclusion of gag gene in a vaccine regimen had modest effects on these odds and was confounded by other covariates. Participants receiving gp140+ gene insert or protein were most often reactive across all serologic HIV tests. Conclusions from this association analysis will provide insight into the possible impact of vaccine design on the HIV diagnostic landscape and vaccinated populations.